2015
DOI: 10.1111/1756-185x.12602
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in lupus nephritis

Abstract: Lupus nephritis (LN) has significant impact on the outcome of patients with systemic lupus erythematosus (SLE). In the absence of any new breakthrough for management of LN over the last few years, using existing treatment modalities in a more effective manner is the mainstay of improving outcomes. For effectively using the drugs, disease activity needs to be assessed accurately and more objectively, which is not possible with present clinical assessment tools. Biomarkers help in accurate assessment of disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 96 publications
(103 reference statements)
0
45
0
Order By: Relevance
“…Thus, an in-depth understanding of the pathogenesis of LN and a search for related biomarkers has important practical significance to the understanding of the severity of LN lesions, judging LN activity, evaluating prognosis, and guiding treatment. In recent years, more and more studies have focused on the pathogenesis of LN and related biomarkers, aiming to improve the prediction of LN activity and the sensitivity and specificity of disease progression [22]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an in-depth understanding of the pathogenesis of LN and a search for related biomarkers has important practical significance to the understanding of the severity of LN lesions, judging LN activity, evaluating prognosis, and guiding treatment. In recent years, more and more studies have focused on the pathogenesis of LN and related biomarkers, aiming to improve the prediction of LN activity and the sensitivity and specificity of disease progression [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Immune complex deposition may induce a large number of inflammatory cytokines in the initial disease stage, resulting in lupus glomerulonephritis. IL-6 is a kind of inflammatory factor mainly secreted by T cells and macrophages, which plays an important role in activating T cells and B cells [22]. Cash et al [23] demonstrated that IL-6 knockout significantly alleviate the symptoms of proteinuria, hematuria, and lymphocyte infiltration in LN mice.…”
Section: Discussionmentioning
confidence: 99%
“…These new classification criteria take into account additional forms of cutaneous lupus and newly described autoantibodies, which may provide further guidance in clinical judgment of SLE. New promising biomarkers for SLE are currently under development, including microRNA [25], presence of urinary immune cells [26], and genetic biomarkers such as specific polymorphisms of MHC, interferon responsive factors, and integrins [27]. Together with updated classification criteria and new biomarkers, we are hopeful to see an increase in certainty of diagnosis for variable presentations of SLE.…”
Section: Discussionmentioning
confidence: 99%
“…As cytokines are important participants in pathogenesis of LN, they are tested for their potential biomarker ability (Misra & Gupta, 2015). Autoantibodies were proved to play a pivotal role in LN (Rekvig & Nossent, 2003).…”
Section: Discussionmentioning
confidence: 99%